Two new isostructural mercury(II) complexes involving the N‐heterocyclic 1‐[(benzotriazol‐1‐yl)methyl]‐1H‐1, 3‐imidazole ligand: syntheses, structures and properties. Issue 4 (6th March 2017) - Wei, Xu; Li, Jian-Hua; Huang, Qiu-Ying; Meng, Xiang-Ru
Abstract : Two new isostructural mercury(II) halide complexes based on 1‐[(benzotriazol‐1‐yl)methyl]‐1 H ‐1, 3‐imidazole (bmi) have been prepared and structurally characterized. Both complexes exhibit a mononuclear structure, in which the bmi ligands coordinate to Hg II ions in monodentate modes. Abstract : The unsymmetrical N‐heterocyclic ligand 1‐[(benzotriazol‐1‐yl)methyl]‐1 H ‐1, 3‐imidazole (bmi) has three potential N‐atom donors and can act in monodentate or bridging coordination modes in the construction of complexes. In addition, the bmi ligand can adopt different coordination conformations, resulting in complexes with different structures due to the presence of the flexible methylene spacer. Two new complexes, namely bis1‐[(benzotriazol‐1‐yl)methyl]‐1 H ‐1, 3‐imidazole‐κ N 3 dibromidomercury(II), [HgBr2 (C10 H9 N5 )2 ], and bis1‐[(benzotriazol‐1‐yl)methyl]‐1 H ‐1, 3‐imidazole‐κ N 3 diiodidomercury(II), [HgI2 (C10 H9 N5 )2 ], have been synthesized through the self‐assembly of bmi with HgBr2 or HgI2 . Single‐crystal X‐ray diffraction shows that both complexes are mononuclear structures, in which the bmi ligands coordinate to the Hg II ions in monodentate modes. In the solid state, both complexes display three‐dimensional networks formed by a combination of hydrogen bonds and π–π interactions. The IR spectra and PXRD patterns of both complexes have also been recorded.